Type 2 diabetes and cognitive functions in patients with chronic cerebrovascular diseases - Marine M. Tanashyan ("Consilium Medicum" Publishing house, 2021)
Background. Type 2 diabetes (Т2DM) both directly and indirectly impacts the development of morphological and functional changes of the central nervous system.